2023
DOI: 10.3390/jcm12165418
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Zygomatic Implant Placement Assisted by Dynamic Computer-Aided Surgery: A Systematic Review and Meta-Analysis

Shengchi Fan,
Gustavo Sáenz-Ravello,
Leonardo Diaz
et al.

Abstract: Purpose: The present systematic review aimed to investigate the accuracy of zygomatic implant (ZI) placement using dynamic computer-aided surgery (d-CAIS), static computer-aided surgery (s-CAIS), and a free-hand approach in patients with severe atrophic edentulous maxilla and/or deficient maxilla. Methods: Electronic and manual literature searches until May 2023 were performed in the PubMed/Medline, Scopus, Cochrane Library, and Web of Science databases. Clinical trials and cadaver studies were selected. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…Zygomatic implants are another graftless option; however, their placement is technically challenging and there are no Food and Drug Administration-approved surgical guides for this procedure. 6 There is also some concern expressed with the placement of unilateral zygomatic implants for partial arch defects given the lack of evidence and concern for mechanical instability of the long lever arm. SPIs offer more flexibility compared to other salvage options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zygomatic implants are another graftless option; however, their placement is technically challenging and there are no Food and Drug Administration-approved surgical guides for this procedure. 6 There is also some concern expressed with the placement of unilateral zygomatic implants for partial arch defects given the lack of evidence and concern for mechanical instability of the long lever arm. SPIs offer more flexibility compared to other salvage options.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, non-vascularized bone grafting success is often unpredictable and may be limited by the constraints of the soft tissue envelope. Zygomatic implants are another graftless option; however, their placement is technically challenging and there are no Food and Drug Administration-approved surgical guides for this procedure 6 . There is also some concern expressed with the placement of unilateral zygomatic implants for partial arch defects given the lack of evidence and concern for mechanical instability of the long lever arm.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on using different guiding techniques to assist with ZI placement to increase intraoperative accuracy and safety 29–33 . Placement of ZIs has become more accurate with the use of surgical navigation systems, while also allowing for implementation of the restorative plan into the implant position 34 . A study by Wu and colleagues 32 in a total of 221 ZI placements in atrophic edentulous using the commercial dynamic navigation system, showed a deviation of 2.64°.…”
Section: Discussionmentioning
confidence: 99%
“…For the static surgical guide, 29,30 a modified customized template with double sleeves has been recently used and achieved acceptable accuracy in placing ZI. More clinical studies need to be investigated of the feasibility of dynamic and static systems for QZP 34 . A recent systematic review and meta‐analysis has shown acceptable clinical accuracy of ZI placement with the assistance of static dynamic systems through real‐time visualization and tracking techniques 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation